Analisa Perhitungan Kerja Aktual Mesin Bubut Pada Proses Pembuatan Nozzle Di Cv. Cahaya Abadi - Jihad Firdaus; Oleh Oleh (Peneliti.net, 2023)
In the business world there is very competitive competition so that companies are required to optimize work in various aspects, be it machines or others. Machine work can be optimized through design, maintenance and repair. CV. Cahaya Abadi was established in Karawang No.38 on 24 October 2008. The company started its commercial activities in December 2008. One of the industrial sectors in the Indonesian economy is the machinery and base metal industry. In the Decree of the Minister of Industry No. 19/M/I/1986, the machine and base metal industry has the characteristics of using machines and base metal and is not labor intensive. One type of basic metal and machine industry is the machine tool industry. The purpose of implementing Practical Work at CV. Cahaya Abadi, namely knowing and learning how to make nozzles by looking directly at the field and through nozzle specifications and calculating the actual work of a lathe by comparing design data and actual data in the field. Results that can have dimensions: Workpiece length 53 mm, by forming materials of different lengths and diameters. On the left side is 25 mm long with a diameter of 33.3 mm. In the center is 4 mm long with a diameter of 37.3 mm. On the right side it is 24 mm long with a diameter of 31.3 mm. Aftermarket coil, performance, scooter vespa PX 150.